What’s the matter with Benjamin O. Flower? - Jean-Louis Marin-Lamellet (European Journal of American Studies)
This article proposes a reconstructive understanding of Populism from the perspective of Boston reform editor Benjamin O. Flower, one of its main publicists. It purposes both to recapture the meaning of “Populism” as it was understood in the 1890s and to trace its fate at the beginning of the 20th century - the ambiguous evolution of Flower, from champion of radical reforms to anti-Catholic crusader at the end of his life, will be used as a case study to examine how and why Populism might overlap with paranoid-style politics. This paper argues that such intellectual trajectories as Flower’s should not be dismissed as the expression of populist psychopathology but can be best understood as the byproduct of ideological conflicts within Progressivism. Populism could then be considered as just one moment in the confrontation between the more radical antimonopoly strand of Progressivism and the managerial liberalism fostered by the more technocratic elements among Progressives.